Effect of lyophilized heterologous seminal plasma supplementation on Marwari stallion epididymal spermatozoa during 24 hours cool storage - RAM, VACHNA; JHAMB, DINESH; GAUR, MITESH; KUMAR, NAVEEN; TALLURI, THIRUMALA RAO; SOLANKI, OMPRAKASH; JUNEJA, ROHIT; PARGI, KALPESH KUMAR; NANDAN, DEVKI; ARORA, SHARAD; VYAS, HIMANSHU (The Indian Journal of Animal Sciences, 2024)
A study was carried out to investigate the effect of storage of testes-epididymis complex at 5oC for 24 h and supplementation of lyophilized heterologous seminal plasma (LHSP) at different concentrations on the sperm quality during cool storage. Six pairs of testicles were collected immediately after orchiectomy from six stallions. One testes-epididymis (F1) was immediately processed for sperm retrieval and second testes-epididymis (F2) complex of each stallion was stored at 5℃ for 24 h. Spermatozoa were harvested from the epididymis by flotation technique and evaluated. Highly significant difference was observed among mean values of progressive motility (%) of epididymal sperm after 0 and 24 h of testicular-epididymal complex storage at 5°C, while no significant difference was observed among mean values of live sperm, membrane integrity and acrosomal integrity (%). Both epididymal sperm suspensions were supplemented with skim milk glucose semen extender fortified with different concentrations (0, 2, 5 and 10 mg/ml) of LHSP and cooled for 24 h. Sperm suspension evaluation at 0, 12 and 24 h of cool storage revealed that addition of 2 mg/ml LHSP has beneficial effect as compared to control on progressive motility and HOST in both epididymal sperm suspension at 12 h and 24 h of cool storage at 5℃. From the current study, it was inferred that the sperm quality was not deteriorated even after the sperm retrieval after 24 h from the epididymis on storage at 5℃. Further, LHSP supplemented @2 mg/ml originated from good fertility stallion is the suitable concentration for cool-storage of equine epididymal sperm suspension.